Stent Balloon Entrapment At Left Main Stem; A Low Resource Setting Approach - Karunaratne, Shanike; Hewarathna, Uditha; Kodithuwakku, Naradha; Dolapihilla, Srinath; Mayurathan, Gnanamoorthy; Jayawardena, Rosy (Nepalese Heart Journal, 2015)
A 60 year old, male patient underwent an elective percutaneous coronary angioplasty and stenting of mid circumflex coronary artery lesion at the origin of second obtuse marginal artery. The bare metal stent deployed in a partially inflated state due to a tight calcific area with subsequent stent balloon entrapment inside the stent by the calcified plaque. It was entrapped entering the left main stem in the partially withdrawn state. With impending surgical retrieval progressive supra burst pressure dilatation attempted to dilate the entrapped segment, final supra burst pressure with successful retrieval. This case highlight the steps to attempt in a low resource setting and final supra burst dilatation of a same stent balloon to overcome an entrapped vessel segment before surgical retrieval options. DOI: http://dx.doi.org/10.3126/njh.v12i1.12342 Nepalese Heart Journal Vol.12(1) 2015: 31-36